2016
DOI: 10.3109/21678421.2015.1131832
|View full text |Cite
|
Sign up to set email alerts
|

The role of mental health and self-efficacy in the pain experience of patients with amyotrophic lateral sclerosis

Abstract: Complex interactions between pain, depression, and anxiety impact quality of life in patients with ALS. Psychological approaches to pain control may be useful. This study explored the role of self-efficacy in mitigating pain. Individuals registered with the Agency for Toxic Substances and Disease Registry National ALS Registry and who experienced pain were invited to participate in an online survey. Subjects completed the Brief Pain Inventory-Short Form, Hospital Anxiety and Depression Scale, and Chronic Pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
2
14
0
2
Order By: Relevance
“…(4) The moderate severity of cramps in this series (5.2/10) is comparable to the prior single center study where most rated their pain as “moderate” and two ALS cramp treatment trials; 4.0/10(14) and 63.5/100(15). The average cramp frequency the patients in our study reported was 5.3 per day, which is higher than the 46 per month reported in the natural history study, being more comparable to the frequencies reported in treatment trials; 5.9(14) and 4.0(15).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…(4) The moderate severity of cramps in this series (5.2/10) is comparable to the prior single center study where most rated their pain as “moderate” and two ALS cramp treatment trials; 4.0/10(14) and 63.5/100(15). The average cramp frequency the patients in our study reported was 5.3 per day, which is higher than the 46 per month reported in the natural history study, being more comparable to the frequencies reported in treatment trials; 5.9(14) and 4.0(15).…”
Section: Discussionsupporting
confidence: 76%
“…(4) Cramps have been reported by 67 to 95 percent of ALS patients. (1, 5) A recent study focused on understanding pain in ALS showed that of those patients who report pain, 67% attribute their pain to cramps alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible direct detrimental effect of antiepileptic drugs on ALS onset cannot be excluded, although neuroprotective effects of gabapentin and valproic acid have been found in ALS mouse models [20,21] , which were confirmed in clinical trials on humans [22,23] . The detrimental effect led us to suppose also that ALS patients were treated with these drugs because they experience neuropathic pain during the onset period, as reported in previous studies [24][25][26] .…”
Section: Discussionmentioning
confidence: 94%
“…Депрессивные нарушения отмечаются почти у половины больных БАС -в 47% случаев, из них бóльшая часть (до 30%) принимают антидепрессанты [39,40]. Показано, что при сопутствующей депрессии болевой синдром у таких пациентов наблюдается достоверно чаще, верно и обратное взаимоотношение [39,41]. Развитие аффективных расстройств, с одной стороны, обусловлено осознанием наличия неизлечимого и неуклонного прогрессирующего заболевания [39,40], а с другой -связано с различными патофизиологическими механизмами [17], недостаточно изученными на сегодняшний день.…”
Section: эпидемиология и особенности болевого синдромаunclassified